Современное состояние питьевого водоснабжения Запорожской области - Севальнев, А.И.; Зыкин, О.В.; Богдановский, В.В.; Шинкарь, А.В. (Актуальні проблеми транспортної медицини, 2009)
У статті надано аналіз сучасного стану питного водопостачання населення Запорізької області. Представлено систему оцінки ризиків для запобігання споживання недоброякісною питною водою. In article the analysis of a modern status of drinking water supply of the population of the Zaporozhye region is presented. The system of an estimation of risks for prevention of consumption by substandard drinking water is presented.